Korelasi Kompetensi Pedagogik Guru Terhadap Hasil Belajar Siswa Kelas VIII.1 Pada Pembelajaran Seni Budaya (Musik) Di SMP Negeri 2 Batusangkar - Yolanda Aurora Hartini Putri; Esy Maestro; Yos Sudarman (SENDRATASIK UNP, 2019)
This article aims to determine the effect of teacher’s pedagogical competence on student learning outcomes in learning music art at SMPN 2 Batusangkar. The type of this research was quantitative research with a correlational method. The techniques used in order to adjust the research instruments were questionnaire and documentation instruments. The steps taken in analyzing data were quantifying data. The results of the study showed that there was a relationship or correlation between pedagogical competencies towards student learning outcomes at SMPN 2 Batusangkar. This was evidenced by the results through the questionnaire. It was found that 32% or as many as 11 students who stated that pedagogic competence always affects student learning outcomes, 66% or as many as 23 students argued frequently, while students who answer sometimes affect student learning outcomes like 0% or 0 students, then 0% of students answered rarely and 2% answered never. In summary, pedagogic competency towards students learning outcomes had a perfect correlation or relationship to student learning outcomes learning art music which was stated by the determinant coefficient value (r2) of 0.820 or 82% while 18% was influenced by other factors thus H0 was rejected and H1 accepted.